Estudio de mercado para la producción y comercialización de aceite de coco orgánico extra virgen en el cantón La Maná, provincia de Cotopaxi - Amen Moreta, Julissa Lilibeth (2023)
The main objective of this investigation was to carry out a market study in order to establish the production and commercialization of extra virgin organic coconut oil in La Maná canton. In addition, the realization of this project has a positive impact on the economic sector by creating new job placement and benefiting local vendors with affordable prices, so that they obtain more profits. It means that the creation of a producer and marketer microenterprise will contribute to the productive development of the Lamanense population. A set of very important methods were also used. The methods are related with the formative, field, purposeful, bibliographical, and diagnostic research which allowed to determine an approach to new effective strategies and to achieve a financial demand by providing a high quality product. The results of the current market study for the production and commercialization were obtained by conducting surveys to the merchants formed by 14 establishments in the urban area of the canton, as well as 382 population that are considered as consumers of the product. To estimate the current demand, the obtained results in table 23 during the year 2022 was taken into account. The demand for coconut oil was 2,730 units per month and 32,760 units in the year. To obtain the projected demand for industrially processed coconut oil (Refined) which would be 13,138 units and 23,164 units for artisanally processed coconut oil (Organic), in the year 2026, a growth rate of 2.6% was applied and the results reveal an unsatisfied demand of -11.556,00 for artisanally processed coconut oil (Organic). The current offer of the product was made through the obtained data from the survey applied to merchants or sellers of coconut oil which shows a total offer of 22.146 units of coconut oil. From the last data, 12.828 units are coconut oil industrially processed (Refined), 9.348 units of artisanally processed coconut oil (Organic), and offered by 14 merchants or sellers of the product. In addition, the internal factors were identified, defining the strengths and weaknesses, as well as the external ones, defining the opportunities and threats, according to strategies.